The Meaning of the Song “Alamate Anak Sholeh” in the Perspective of Da'wah Message - Indah Sariyanti; Nuris Asro'atul Hasanah; Nidya Agustin Beni Prasetyo (Sahafa Journal of Islamic Communication, 2024)
This article aims to analyze the song "Alamate Anak Sholeh" from the perspective of Islamic da'wah, using Charles Sanders Pierce's semiotic approach to uncover the symbolic meanings within its lyrics. The primary focus is on four key aspects related to pious children, including moral values, religious education, and character development in an Islamic context. Secondary data from books and journal articles are utilized to support this analysis, indicating that the song serves not only as entertainment but also as an effective medium for disseminating religious messages within society. The research yields a profound understanding of the role of music as a medium of da'wah capable of influencing religious values and morality in popular culture, affirming that music holds significant potential in shaping religious awareness in the contemporary era.   Keywords: Meaning song; Da'wah Message; Semiotic